Treatment of digestate from a co-digestion biogas plant by means of vacuum evaporation: Tests for process optimization and environmental sustainability - Chiumenti, A.; da Borso, F.; Chiumenti, R.; Teri, F.; Segantin, P. (Waste management (Elmsford), 2013)
•Pilot vacuum evaporation systems were tested on digestate from a 1MWe biogas plant.•Single and two-stage configurations, with and without acidification, were tested.•Concentrate resulted 20% and 6% of mass in single and two-stage systems respectively.•Liquid and solid concentrates were obtained by first and second stage respectively.•With acidification about 98% of input N was transferred to concentrate (55gTKN/kg). Vacuum evaporation consists in the boiling of a liquid substrate at negative pressure, at a temperature lower than typical boiling temperature at atmospheric conditions. Condensed vapor represents the so called condensate, while the remaining substrate represents the concentrate. This technology is derived from other sectors and is mainly dedicated to the recovery of chemicals from industrial by-products, while it has not been widely implemented yet in the field of agricultural digestate treatment. The present paper relates on experimental tests performed in pilot-scale vacuum evaporation plants (0.100 and 0.025m3), treating filtered digestate (liquid fraction of digestate filtered by a screw-press separator). Digestate was produced by a 1MWe anaerobic digestion plant fed with swine manure, corn silage and other biomasses. Different system and process configurations were tested (single-stage and two-stage, with and without acidification) with the main objectives of assessing the technical feasibility and of optimizing process parameters for an eventual technology transfer to full scale systems. The inputs and outputs of the process were subject to characterization and mass and nutrients balances were determined. The vacuum evaporation process determined a relevant mass reduction of digestate. The single stage configuration determined the production of a concentrate, still in liquid phase, with a total solid (TS) mean concentration of 15.0%, representing, in terms of mass, 20.2% of the input; the remaining 79.8% was represented by condensate. The introduction of the second stage allowed to obtain a solid concentrate, characterized by a content of TS of 59.0% and representing 5.6% of initial mass. Nitrogen balance was influenced by digestate pH: in order to limit the stripping of ammonia and its transfer to condensate it was necessary to reduce the pH. At pH 5, 97.5% of total nitrogen remained in the concentrate. This product was characterized by very high concentrations of total Kjeldhal nitrogen (TKN), 55,000mg/kg as average. Condensate, instead, represented 94.4% of input mass, containing 2.5% of TKN. This fraction could be discharged into surface water, after purification to meet the criteria imposed by Italian regulation. Most likely, condensate could be used as dilution water for digestion input, for cleaning floor and surfaces of animal housings or for crop irrigation. The research showed the great effectiveness of the vacuum evaporation process, especially in the two stage configuration with acidification. In fact, the concentration of nutrients in a small volume determines easier transportation and reduction of related management costs. In full scale plants energy consumption is estimated to be 5–8kWhe/m3 of digestate and 350kWht/m3 of evaporated water.